A novel approach to synthesize porous graphene sheets by exploring KOH as pore inducing agent as well as a catalyst for supercapacitors with ultra-fast rate capability. (July 2021) - Nanaji, Katchala; Sarada, B.V.; Varadaraju, U.V.; N Rao, Tata; Anandan, Srinivasan
Abstract: In the present study, an earth-abundant bio-waste is effectively transformed into porous graphene sheets at a low temperature of 900 °C by utilizing Potassium hydroxide (KOH) as an activation agent to create porosity as well as a catalyst to induce graphitization by a simple synthetic approach. The resulted carbon material possesses good textural properties such as high specific surface area (2308 m 2 /g), high pore volume (1.3 cm 3 /g), graphene sheet-like morphology with an interlayer d-spacing of 0.345 nm and a highly ordered sp 2 carbon as evidenced from detailed textural analysis. A detailed mechanism for the formation of graphene sheets is further explored. Owing to the multiple synergistic properties, the material has been tested as an efficient electrode material for supercapacitor application and it delivered a high specific capacitance of 240 F g −1 at 1 A/g. Furthermore, the assembled symmetric supercapacitor exhibits ultra-fast rate capability of 87% capacitance retention at high current rates (50 A/g), exceptional cyclic stability (93% retention after 25, 000 cycles) and displays outstanding energy density of 21.37 W h kg −1 at a high power density of 13, 420 W kg −1 . The strategy developed here reveals a facile, low-cost, eco-friendly design of graphene sheets at large scale production, where the synthetic approach can be applied as a versatile method to prepare graphene sheets from any carbon sources using KOH activation. Graphical abstract: Image 1 Highlights: Biomass conversion into porous graphene-like carbon sheets at a low temperature of 900 °C. Investigating the mechanism for graphene sheet formation using KOH. The material exhibits a graphene sheet-like morphology with an interlayer d-spacing of 0.345 nm and ID /IG of 0.315. A specific capacitance of 240 F g −1 was achieved with ultra fast rate capability and outstanding cyclic stability. Displays a high gravimetric energy density of 28.92–21.37 Wh kg −1 at a power density range of 670–13, 426 W kg −1 .